Geographic Information System Using Node Combination Based on Dijkstra's Algorithm for Determining the Shortest Tsunami Evacuation Route in Palu Bay: Rancang Bangun Sistem Informasi Geografis Menggunakan Kombinasi Node Berbasis Algoritma Dijkstra Pada Penentuan Jalur Terpendek Evakuasi Tsunami Di Teluk Palu - Angreni, Dwi Shinta; Budiman, Wahyu; Anshori, Yusuf; Wirdayanti, Wirdayanti; Bintana, Rizqa Raaiqa (Foristek, 2024)
Indonesia, an archipelagic country situated on the Equator and surrounded by the Ring of Fire, is highly susceptible to natural disasters such as tectonic earthquakes and volcanic eruptions. Palu, one of Indonesia's seismically active regions, is traversed by the Palu-Koro Fault, which has the potential to trigger strong earthquakes and tsunamis, as evidenced by the 7.4-magnitude earthquake in September 2018. To mitigate disaster risks, it is crucial to understand community vulnerability and utilize Geographic Information System (GIS) technology. This study designs a GIS-based system using the modified Dijkstra's Algorithm to determine the shortest tsunami evacuation routes in Palu. Testing results indicate that the system is effective, with a user satisfaction rate of 89.33% and satisfactory route prediction accuracy compared to Google Maps. The system can be relied upon to help communities find the nearest evacuation routes, thereby enhancing safety and preparedness in the face of potential disasters.